CACNA1C rs1006737, Threatening Life Events, and Gene–Environment Interaction Predict Major Depressive Disorder - Zhao, Mingzhe; Yang, Jiarun; Qiu, Xiaohui; Yang, Xiuxian; Qiao, Zhengxue; Song, Xuejia; Wang, Lin; Zhao, Erying; Yang, Yanjie; Cao, Depin (Frontiers in Psychiatry, 2020)
Introduction: CACNA1C rs1006737 is a novel variants in discovery of replicable associations in major depressive disorder(MDD). However, there have been no specific studies considered effect of environmental pathogens to date examining its clinical significance. In this study we investigated the interaction effect between CACNA1C rs1006737 polymorphism and threatening life events (TLEs) in MDD and carried out a meta-analysis of published findings. Methods: A total of 1177 consecutive participants were genotyped. Information on exposure to TLEs, socio-demographic data, and history of psychological problems among first-degree relatives was collected. MDD was diagnosed according to the Chinese version of the 24-item Hamilton Rating Scale for Depression. Results: There was a significant interaction effect between CACNA1C rs1006737 polymorphism and TLEs in MDD. A dose-response relationship was found between CACNA1C rs1006737 genotypes and TLEs in MDD. The results of the meta-analysis showed that CACNA1C rs1006737 genotypes interacted with TLEs in MDD. Conclusion: CACNA1C rs1006737 genotype and previous exposure to TLEs interact to influence the risk of developing MDD. We propose that CACNA1C rs1006737 may represent a target for novel pharmacological therapies to prevent or treat MDD.